Evolution of СD95+-cells in peripheral blood of patients with ovarian cancer in during the combined treatment - N. G. Kormosh; T. N. Zabotina (Опухоли женской репродуктивной системы, 2014)
Paper deals with the content of CD95+-cells in the blood of patients with ovarian cancer and benign tumors. Found that patients with a malignant process and low CD95+-cells before treatment and during chemotherapy have a poor survival. The initial increase in the relative level CD95+- cells has no effect on survival, increasing the relative level CD95+-cells during chemotherapy is associated with poor survival. Concluded that the CD95 can not be a factor in the forecast, but the reaction of the organism to maintain its level within the physiological range in the treatment of ovarian cancer patients can achieve significantly better long-term results.